Neuroprotective Effects and Mechanisms of Senegenin, an Effective Compound Originated From the Roots of Polygala Tenuifolia - Chen, Zhe; Yang, Yu; Han, Ying; Wang, Xijun (Frontiers in Pharmacology, 2022)
Senegenin is the main bioactive ingredient isolated from the dried roots of Polygala tenuifolia Willd. In recent years, senegenin has been proved to possess a variety of pharmacological activities, such as anti-oxidation, anti-inflammation, anti-apoptosis, enhancement of cognitive function. Besides, it has a good development prospect for the treatment of neurodegenerative diseases, depression, osteoporosis, cognitive dysfunction, ischemia-reperfusion injury and other diseases. However, there is no systematic literature that fully demonstrates the pharmacological effects of senegenin. In order to meet the needs of new drug research and precise medication, this review summarizes the neuroprotective effects, mechanisms and toxicity of senegenin based on the literatures published from the past two decades. In addition, an in-depth analysis of the existing problems in the current research as well as the future research directions have been conducted in order to provide a basis for the clinical application of this important plant extract.